Seafloor megafauna in the Central Arctic during POLARSTERN cruise PS80 (ARK-XXVII/3, IceArc) to the Central Arctic Ocean in August and September 2012 - Rybakova, Elena; Kremenetskaia, Antonina; Vedenin, Andrey; Boetius, Antje; Gebruk, Andrey V (Supplement to: Rybakova, E et al. (2019): Deep-sea megabenthos communities of the Eurasian Central Arctic are influenced by ice-cover and sea-ice algal falls. PLoS ONE, 14(7), e0211009, https://doi.org/10.1371/journal.pone.0211009, 2018)
Quantitative camera surveys of benthic megafauna were carried out during the expedition ARK-XXVII/3 to the Eastern Central Arctic basins with the research icebreaker Polarstern in summer 2012 (2 August-29 September). Nine transects were performed for the first time in deep-sea areas previously fully covered by ice, four of them in the Nansen Basin (3571-4066m) and five in the Amundsen Basin (4041-4384m). At seven of these stations benthic Agassiz trawls were taken near the camera tracks for species identification.